Oxide 2D electron gases as a route for high carrier densities on (001) Si - Kornblum, Lior; Jin, Eric N.; Kumah, Divine; Ernst, Alexis T.; Broadbridge, Christine; Ahn, Chong H.; Walker, Fred (Applied Physics Letters, 2015)
Two dimensional electron gases (2DEGs) formed at the interfaces of oxide heterostructures draw considerable interest owing to their unique physics and potential applications. Growing such heterostructures on conventional semiconductors has the potential to integrate their functionality with semiconductor device technology. We demonstrate 2DEGs on a conventional semiconductor by growing GdTiO3-SrTiO3 on silicon. Structural analysis confirms the epitaxial growth of heterostructures with abrupt interfaces and a high degree of crystallinity. Transport measurements show the conduction to be an interface effect, ∼9 × 1013 cm-2 electrons per interface. Good agreement is demonstrated between the electronic behavior of structures grown on Si and on an oxide substrate, validating the robustness of this approach to bridge between lab-scale samples to a scalable, technologically relevant materials system. © 2015 AIP Publishing LLC.
16 citations (Crossref) [2023-10-31] Citation Key Alias: pop00055 tex.type: [object Object]
Keywords: D electrons; Degree of crystallinity; Electron gas; Electronic behaviors; Heterojunctions; Interface effect; Materials systems; Oxide heterostructures; Oxide substrates; Semiconducting silicon; Semiconductor devices; Silicon; Transport measurements; Two dimensional electron gas; dept.phy

Domain pinning and valence state switching in Pb(Zr0.2Ti0.8)O3/La0.8Sr0.2MnO3 heterostructures - Su, Dong; Vaz, Carlos A. F.; Segal, Y.; Walker, Fred; Ahn, Chong H.; Han, M-G; Sawicki, Monica; Broadbridge, Christine (Microscopy and Microanalysis, 2011)
0 citations (Crossref) [2023-10-31] Citation Key Alias: pop00142 tex.type: [object Object]
Keywords: dept.phy

Origin of 90° domain wall pinning in Pb(Zr0.2Ti0.8)O3 heteroepitaxial thin films - Su, Dong; Meng, Qingping; Vaz, Carlos A. F.; Han, Myung-Geun; Segal, Y.; Walker, Fred; Sawicki, Monica; Broadbridge, Christine; Ahn, Chong H. (Applied Physics Letters, 2011)
We describe a transmission-electron-microscopy study of the ferroelectric domains in an epitaxial Pb(Zr0.2Ti0.8)O3 (PZT) film grown on La0.7Sr0.3MnO3/SrTiO 3(001). We directly observe the pinning of 90 domain walls by pairs of misfit dislocations, respectively, with Burgers vectors a [100] and a [001]. Model calculations based on the elastic theory confirm our finding that, in addition to the depolarization field surrounding the dislocation, the strain field of misfit dislocation-pairs plays the primary role in the formation and pinning of a domains. © 2011 American Institute of Physics.
48 citations (Crossref) [2023-10-31] Citation Key Alias: pop00042 tex.type: [object Object]
Keywords: Depolarization fields; Domain walls; Domain-wall pinning; Elastic theory; Epitaxial growth; Ferroelectric domains; Ferroelectricity; Heteroepitaxial thin films; Heterojunctions; Lanthanum compounds; Lead; Manganese oxide; Model calculations; PZT; Strain fields; Zirconium; dept.phy

The atomic structure and polarization of strained SrTiO3/Si - Kumah, Divine; Reiner, James W.; Segal, Y.; Kolpak, Alexie M.; Zhang, Zhizhi; Su, Dong; Zhu, Yimei; Sawicki, Monica; Broadbridge, Christine; Ahn, Chong H.; Walker, Fred (Applied Physics Letters, 2010)
For thin film devices based on coupling ferroelectric polarization to charge carriers in semiconductors, the role of the interface is critical. To elucidate this role, we use synchrotron x-ray diffraction to determine the interface structure of epitaxial SrTiO3 grown on the (001) surface of Si. The average displacement of the O octahedral sublattice relative to the Sr sublattice determines the film polarization and is measured to be about 0.05 nm toward the Si, with Ti off-center displacements 0.009 nm away from the substrate. Measurements of films with different boundary conditions on the top of the SrTiO3 show that the polarization at the SrTiO3 /Si interface is dominated by oxide-Si chemical interactions. © 2010 American Institute of Physics.
25 citations (Crossref) [2023-10-31] Citation Key Alias: pop00073 tex.type: [object Object]
Keywords: Atomic structure; Chemical interactions; Crystal atomic structure; Different boundary condition; Ferroelectric polarization; Interface structures; Polarization; Semiconducting silicon compounds; Silicon; SrTiO; Strontium alloys; Sub-lattices; Synchrotron x ray diffraction; Thin film devices; X ray diffraction; dept.phy